Enhancing Spanish speaking skills of undergraduate students with metaverse role-playing - Piriyasurawong, Pornpan (International Journal of Innovative Research and Scientific Studies, 2025)
Speaking is one of the fundamental communicative skills in a language. However, most learners experience problems in speaking a foreign language fluently and lack confidence. This research aims to enhance the Spanish speaking skills of undergraduate students using role-playing as a teaching method and incorporates it into the metaverse, which was designed and created as virtual scenes in Spain, resulting in a Metaverse role-playing approach to enhance Spanish speaking skills. The approach was implemented with a sample group of 34 undergraduate students from Kasetsart University, Thailand, who enrolled in the Spanish for Communication 1 course for the academic year 2023, selected by a simple random sampling method and conducted using a one-group pretest-posttest research design. The findings of this research were: 1) The average post-test score (x-bar) of Spanish speaking skills of undergraduate students after the metaverse role-playing approach was significantly higher than before (pre-test) at the .01 level. 2) The average post-test score (x-bar) of Spanish speaking skills of undergraduate students after using metaverse role-playing was 87.50%, which was higher than the criteria set at 80%, with statistical significance at the .01 level. Therefore, the research concludes that the metaverse role-playing approach enhances students’ learning achievement, thus also enhancing their speaking skills in Spanish.